Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.
Customized for You
we will pick new questions that match your level based on your Timer History
Track Your Progress
every week, we’ll send you an estimated GMAT score based on your performance
Practice Pays
we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
It appears that you are browsing the GMAT Club forum unregistered!
Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club
Registration gives you:
Tests
Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.
Applicant Stats
View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more
Books/Downloads
Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!
Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:
E?
from stat 1=> a^2 = b^2.....insuff take a=1 b=1 and answer is a=|b| yes
take a=-1 and b=1 and answer is a=|b| no
from stat 2 => b=|a| doesn't mean that a=|b|
combine 1 and 2 (seems to me that the statements are saying nothing substantially different)
hope it's E (I'm a bit tired to combine the statements,maybe it will be better if I go to bed )
from (i), b=lcl, which means b^2=c^2. if so, then
a^2+c^2=2b^2
a^2+b^2=2b^2
a^2 =b^2
a = + or - b, which means a = lbl.............. sufficient.
from (ii), b= lal, which also means b^2=a^2
a^2+c^2=2b^2
b^2+c^2=2b^2
c^2=b^2. then again the same process as in (i)
a^2+c^2=2b^2
a^2+b^2=2b^2
a^2 =b^2
a = + or - b, which means a = lbl.............. sufficient.
Don't be fooled by the seemly complexity of this question.
The question asks if a=|b|. With absolute value questions your first relection should be "do we know it's sign?" |b| is non negative. If we aren't able to determine if a is non negative then we can't determine if a=|b|.
Now look at the stem: a^2-b^2=b^2-c^2
and the two choices:
b=|c| and b=|a|
All we know is b is non negative. Do we know anything about a's sign? No! _________________
Keep on asking, and it will be given you;
keep on seeking, and you will find;
keep on knocking, and it will be opened to you.
Don't be fooled by the seemly complexity of this question.
The question asks if a=|b|. With absolute value questions your first relection should be "do we know it's sign?" |b| is non negative. If we aren't able to determine if a is non negative then we can't determine if a=|b|.
Now look at the stem: a^2-b^2=b^2-c^2 and the two choices: b=|c| and b=|a| All we know is b is non negative. Do we know anything about a's sign? No!
It took me just over 60 secs to choose 'E'. Hong's approach reduces this to a less that 10 sec question. Good one, that!
Think it'll be E
as the first statement only proves that a^2 = b^2
for a to equal |b|, we would have to be sure that a is positive which we can't be...
second statement doesn't give any new information
even with both together there is no way of knowing that a is positive
Don't be fooled by the seemly complexity of this question.
The question asks if a=|b|. With absolute value questions your first relection should be "do we know it's sign?" |b| is non negative. If we aren't able to determine if a is non negative then we can't determine if a=|b|.
Now look at the stem: a^2-b^2=b^2-c^2 and the two choices: b=|c| and b=|a| All we know is b is non negative. Do we know anything about a's sign? No!
Honghu, I am not sure if your approach to this particular question is right, because the question is really asking us whether a = b irrespective of their signs, so this can be deduced to is a^2 = b^2.